Study of the population of native shrimp (Cryphiops caementarius) and its effect on its resistance, in the Sama River, Tacna 2021 and 2022 - Viza Chura, Noé Moisés (2023)
The research “Study of the Population of Native Shrimp (Cryphiops caementarius), and its Effect on its Resistance, in the Sama River, Tacna, 2021 and 2022”, which was developed between the mouth of the Sama River and the Cuilona Bridge at 300 meters above sea level. , having as objective: Evaluate the relationship of the population and biological aspects where the species under study (Cryphiops caementarius) develops, and its sustainability in the Tacna Region. In the methodology, it was planned to collect and evaluate the interpretation of the characteristics of the populations, using a 0,50 m half-moon mouth carcal, with a base with a plastic mosquito net, each specimen obtained was examined according to means of quantification, measurement and weighing of each field trip, reaching the following conclusion: Size values and weight, obtained during the years 2021 and 2022 in the Sama River, a maximum of 7,47 cm was given in September 2021 and a minimum of 1,61 cm in January 2021. However, regarding weight, the maximum was 7,01 grams in December 2022 and at least 1,49 grams in January 2021; The highest percentage of ovigerous females occurred in December with 50% of females found.Finally, during the development of the 2021 and 2022 research, it has been possible to observe the resource permanently, which ensures its viability in the Sama River, despite the larval mortality that occurs due to the use of toxic substances by part of poaching fishermen.